CIC‐DUX4 sarcoma diagnosed by fine‐needle aspiration cytology: A case report. Issue 11 (24th October 2018) - Tang, Sherry; Dodd, Leslie G.
Abstract: The CIC‐DUX4 sarcoma is a small round blue cell sarcoma which presents like extraskeletal Ewing sarcoma, but is negative for the EWSR1 gene translocation. The recognition of CIC‐DUX4 sarcomas as an aggressive sarcoma may be challenging in fine needle aspirates or small needle core biopsies. We present a case of a 13‐year‐old female with a fine needle aspiration (FNA) and core needle biopsy (CNB) of a thigh mass showing CIC‐DUX4 sarcoma. Cytologic findings include tumor cells with high nuclear to cytoplasmic (N:C) ratio, eccentric nuclei and small nucleoli. The tumor cells were arranged in sheets and singly dispersed with background necrosis. Mitotic figures and apoptosis were present. These findings are similar to cases previously reported. Other reported findings of spindled nuclei, clear cell change and lobular growth pattern were not seen in our case. Immunohistochemical stains showed tumor cells positive for CD99, WT1, vimentin and negative for pancytokeratin, desmin and myogenin, which is the pattern similar to cases previously reported. However, our case was also positive for BCL‐2. Fluorescence in situ hybridization (FISH) was negative for EWSR1 and SS18 (SYT) rearrangements and positive for CIC gene rearrangement. On balance, if the following features are seen: (1) a small round blue cell tumor with histomorphology more atypical than that of Ewing sarcoma, (2) cytoplasmic CD99 staining, nuclear WT1 positivity, negative keratin, desmin and myogenin; and (3) EWSR1 rearrangement negative by FISH, then molecular testing for CIC‐DUX4 sarcoma should be considered.